WEBSITE-BASED TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE FOR LEARNING PREPARATION OF SCIENCE TEACHERS - Insih Wilujeng; Nugan Tadeko; Wipsar Sunu Brams Dwandaru (Jurnal Cakrawala Pendidikan, 2020)
This study produces technological pedagogical and content knowledge (TPACK) instruments, which conventionally use print modules. The aims of this study were 1) to develop appropriate website-based TPACK instruments, and 2) to determine the effect of the produced website-based TPACK instruments toward the pedagogy competence of Science teachers in their learning preparation in the classroom. The methodology used was based on the ADDIE stages which stand for analyze, design, develop, implement, and evaluate. The results of this study include 1) instructions for producing TPACK instruments based on the results of synthesis; 2) instructions for making a website format based on the synthesis results; 3) TPACK framework design in website content; 4) TPACK instruments validation results; and 5) website validation results. Moreover, limited and field tests were conducted upon the website-based TPACK instruments to determine their effect toward the pedagogy competence of Science teachers.  Quantitatively, the TPACK instruments scored 70 out of 76, while the website scored 60 out of 90. Finally, the limited and field tests results showed that website-based TPACK instruments positively affect the pedagogy competence of Science teachers in their learning preparation in the classroom with an overall Good category and a Very Good category for the usage evaluation from the users.